Anesthesia and perioperative challenges for surgical separation of thoraco-omphalopagus twins: case report - Freitas,Milton Halyson Benevides de (2019)
Abstract Background and objectives: Conjoined twins are monozygotic twins physically joined at some part of the body. This is a rare phenomenon, estimated between 1:50,000 and 1:200,000 births. The objective of this report is to present the anesthetic management and the perioperative challenges for a separation surgery. Case report: Thoraco-omphalopagus twins were diagnosed by ultrasound and were followed by the fetal medicine team of the service. After 11 h of cesarean surgery, the pediatric surgical team chose to separate the twins. They were monitored with cardioscopy, oximetry, capnography, nasopharyngeal thermometer, urinary output, and non-invasive blood pressure. We chose inhaled induction with oxygen and 4% Sevoflurane. T1 patient was intubated with a 3.5 uncuffed endotracheal tube, and, after three unsuccessful intubation attempts of patient T2, a number 1 laryngeal mask was used. After securing the twins’ airway, the induction was supplemented with fentanyl, propofol, and rocuronium. Mechanical ventilation in controlled pressure mode (6 mL.kg−1) and lumbar epidural (L1-L2) with 0.2% ropivacaine (2.5 mg.kg−1) were used. The pediatric surgical team initiated the separation of the twins via sternotomy, ligation of hepatic vessels. After 2 hours of procedure, the separation was completed, continuing the surgical treatment of T1 and the support of T2 until his death. Conclusions: Conjoined twin separation surgery is a challenge, which requires planning and coordination of a multidisciplinary team during all stages.